Analisis Perbandingan Metode Altman, Grover Dan Zmijewski Dalam Memprediksi Kebangkrutan Perusahaan (Studi Kasus Perusahaan Farmasi Yang Terdaftar Di Bursa Efek Indonesia Periode 2015-2019) - Nela Rahayuni; Ronny Malavia Mardani; Budi Wahono (E-JRM : Elektronik Jurnal Riset Manajemen, 2020)
AbstractThe purpose of this research are: 1) to analyze the comparison of Altman, Grover, and Zmijewski methods in predicting brankruptcy of pharmaceutical sub-sector companies, 2) to find out the most accurate prediction method in predicting bankruptcy sub-sector companies.  The type of research is descriptive with a quantitative approach. The sampling technique uses purposive sampling technique with a total sample of 5 pharmaceutical sub-sector companies. The results shaved that the Altman, Grover and Zmijewski methods are an accurate method in predicting bankruptcy of pharmaceutical companies in Indonesia, with an accucary rate of 100% and an error type of 0%. In addition, if the Altman, Grover and Zmijewski methods are use together, the three prediction methods are able to predict the bankruptcy of pharmaceutical sub-sector companies listed on the Bursa Efek Indonesia. Keywords : pharmaceutical companies, Bankruptcy, Altman Method, Grover Method , Zmijewski Method